Membangun Keunggulan Bersaing Dengan Inovasi Dan Orientasi Kewirausahaan: A Systematic Literature Review - Karina Nindya Krisdiana; Siti Nur Alisa; Muhamad Septian Nurafan; Siti Sri Wulandari; Yessy Artanti (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The increasingly intense business competition, both locally and globally, requires companies to continuously adapt and develop strategies to maintain their competitive advantage. Innovation and entrepreneurial orientation are two key factors that contribute to enhancing business competitiveness. Innovation enables companies to create new products, services, and processes that better meet market demands, while entrepreneurial orientation fosters risk-taking and the exploration of new opportunities. This study employs a Systematic Literature Review (SLR) method to analyze previous research on the relationship between innovation, entrepreneurial orientation, and competitive advantage. Based on a review of 30 articles, findings indicate that companies implementing innovation and possessing a strong entrepreneurial orientation are more likely to achieve and sustain competitive advantages. However, several challenges hinder the implementation of these strategies, including resource constraints, limited access to technology, and low digital literacy among small business actors. The study highlights the importance of integrating innovation and entrepreneurial orientation into business strategies for companies aiming to grow and survive in the era of globalization.